Structural Equation Model for a Relationship between Family Support Systems and Alcohol Addiction Recovery: Mediation Effect of Continuing Care Services - Kyazze, Richard; Natuhamya, Charles; Mwebesa, Edson; Kiyingi, Frank; Musoke, Miph; Tumwesigye, Nazarius Mbona (Journal of Advanced Psychology, 2024)
Purpose: Alcohol use disorder continues to be a public health concern, and even after treatment, the relapse rate is still high. The family support systems are closely related to alcohol addiction recovery. However, studies on psychological mechanisms between the two are rare. Therefore, we aimed to explore the mediating role of continuing care services in the pathway between family support systems and alcohol addiction recovery among individuals with alcohol use disorder. Methods: A total of 196 participants from 5 treatment centers (Butabika National Referral Mental Hospital, Serenity Centre, Recovery Solutions, National Care Centre, and Hope and Beyond) were selected from a target population of 400 individuals. The structural equation modeling approach was used to assess the study objective. Results: The average alcohol addiction recovery status score was 3.03 (SD = 0.95). The mediation analysis indicated that continuing care services mediated the pathway between family support systems and alcohol addiction recovery. Unique Contribution to Theory, Practice and Policy: Motivational enhancement therapy, mutual health support, and cognitive behavioral therapy are key factors in the relationship between family support systems and alcohol addiction recovery.